The Evolution of the Deubiquitinating Enzyme Superfamily - Vlasschaert, Caitlyn (Université d'Ottawa / University of Ottawa, 2016)
Multiple versions of a parent gene can function within molecular systems as gene duplicates (paralogs) and alternatively spliced isoforms. Proteins related in this manner often serve redundant roles, though they can be selectively or randomly prescribed unique functions. The present collection of three manuscripts details the evolution of members of the deubiquitinating enzyme superfamily. The first manuscript delineates the chronology of USP4, USP15 and USP11 emergence and concludes that the presumed ancestor, USP11, is in fact a recent duplicate and that, at minimum, one copy of USP4 or USP15 is required for organismal viability. The second determines that the long and short isoforms of mammalian USP4 are maintained by natural selection to occupy discrete spatial roles. The final manuscript broadens the scope and objectively draws the genealogy of all deubiquitinating enzymes, with emphasis on significant points of functional divergence of paralogs within innate immunity and DNA repair pathways.
Keywords: USP4; molecular evolution; deubiquitinating enzyme; gene family